Application of Shopee E-Commerce in Facing Market Competition in A Company in The Digital Era - Dian Firmansyah, Prado; Ali, Hapzi (Greenation Research & Yayasan Global Resarch National, 2024)
Implementation of E-commerce as a strategy to face market competition in the context of the digital era. Through a case study of a company, analysis is carried out on the implementation of E-commerce in increasing the company's competitiveness in an increasingly competitive market. Qualitative research methods are used to understand the impacts and strategies carried out by companies in adopting E-commerce. The findings show that implementing E-commerce allows companies to expand market reach, increase operational efficiency, and improve customer experience. The practical implication of this research is the importance of integrating digital technology in a company's business strategy to remain relevant and competitive in the digital era. This research provides insight for other companies who want to exploit the potential of E-commerce in facing digital market challenges.